PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN KEAKTIFAN BERTANYA BIOLOGI SISWA KELAS XI IPA 1 SMA NEGERI 1 NGEMPLAK TAHUN PELAJARAN 2011/ 2012 - Dewi, Evita Rosilia; Harlita, Harlita; Ariyanto, Joko (Pendidikan Biologi, 2011)
ABSTRACT - The purpose of this study is to improve student Questioning Participation on Biology teaching by implementation of Active Knowledge Sharing strategy on Blood System Regulation. This research is as classroom action research.  The experiment was conducted in two cycles, with each cycle consisting of the planning, acting, observation, and reflection. Subjects were students of class XI IPA 1 SMA Negeri 1 Ngemplak Tahun Pelajaran 2011/ 2012. Source of data derived from teacher and student information, places and events on going learning activities, and documentation. Techniques and tools of data collection are questionnaire, observation, and interviews. Technical analysis of data is using qualitative descriptive. Data validation is use methods triangulation  Result of the research show  that with action performing brazes to pass through learning strategy purpose  Active Knowledge Sharing  questioning participation  in biology learning in class XI IPA 1 SMA Negeri 1 Ngemplak Tahun Pelajaran 2011/ 2012. It  is gone upon on questionnaire result, observation and interview. The average percentage each indicator of student activities based on observation  for  pre cycle is 42,30%, a cycle of 62,69% and 79,92% for cycle 2. The conclusions that application of  Active Knowledge Sharing  strategy can improve Questioning Participation.   Key words: Active Knowledge Sharing, Questioning Participation  , Biology learning.